International Risk Sharing and Currency Unions : The CFA Zones - Yehoue, Etienne (IMF Working Papers; Working Paper ;, 2005)
This paper explores income and consumption smoothing patterns among the member countries of each of the CFA zones-the CEMAC2 and the WAEMU3-during the period 1980-2000. I find that for the CEMAC, only about 15 percent of shocks to GDP are smoothed through the standard channels (that is, capital market, credit market, and remittances). On the other hand, I find that 44 percent of shocks are smoothed via foreign aid from France, and 5 percent via central bank contributions, while reserves pooling provides no shock smoothing. For the WAEMU, I find that only 13 percent of shocks are smoothed through the standard channels, while 63 percent are smoothed via foreign aid from France, 7 percent via central bank contributions, and no smoothing via reserves pooling. I compare these results with the risksharing pattern in the Unites States. I argue that creating public venture capital at a regional level might help promote free capital flows within each zone and alleviate the apparently insufficient degree of risk-sharing observed through the standard channels.